Analysis of Student Misconceptions on the Solar System Material Using the Four-Tier Test Instrument - Fitriyani, Fitriyani; Atmojo, Idam Ragil Widianto; Yamtinah, Sri (Universitas Pendidikan Indonesia, 2025)
Misconception is a misunderstanding or inaccurate understanding of a certain concept or information. Category misconceptions are still common in elementary school sixth grade students, the occurrence of misconception can be due to several factors. This research aims to identify and discredit misconceptions of elementary school sixth grade students in the eye of solar system material IPA lessons. Data collection method using four-tier test instruments. The approach used in the research is a quantitative approach. The research was carried out at the State SD 2 Nadi Bulukerto district. The population in the study was class VI students. The study sample is 16 students who have studied the material of the Solar System. Data from the research was analyzed using descriptive quantitative analysis. The results of the study showed that misconceptions that occurred in elementary school students belonged to the